Rozłam w Polskiej Partii Socjalistycznej w oświetleniu publicystów „Trybuny” - Czekaj, Katarzyna (Acta Universitatis Lodziensis. Folia Historica, 2008)
"Trybuna" was a magazine founded by a group of PPS (Polish Socialist Party) activists centred around Jozef Pilsudski in November 1906 to propagate the political programme of die faction of “the old” that - after the split in die party - established the PPS-Frakcja Rewolucyjna (Revolutionary Faction). Among the magazine’s columnists one could find the most important writers, i.e. those who belonged to the group centered around Piłsudski (Jodko, Sieroszewski, Filipowicz) as well as Żeromski, Limanowski, Daniłowski, and Orkan. Until the formal split in the party, which took place at the 9"' Congress in November 1906, the articles in “Trybuna” had not vigorously opposed the official party programme. Only later did the columnists of the Revolutionary Faction start strongly opposing the tactical and ideological principles of their former comrades. Although the political programme of the Revolutionary Faction did not formally differ from the PPS agenda as the struggle for influence among party members and labourers excluded the possibility of divergence from the most important socialist demands, ''Trybuna” emphasized those aspects of the programme which constituted the pillars of Pilsudski’s conception. The primary target of the Revolutionary Faction - as it results from articles in “Trybuna" - was to prepare the Polish society for an armed struggle for the independence of Poland, i.e. to train the cadres that could lead the prospective national uprising and to overcome the psychological barrier within the Polish society, which caused the people to be lethargic and passive towards the partitioned. Another distinct matter prevalent from the very beginning in articles of "Trybuna" was the attitude of the Revolutionary Faction towards the revolutionary movement in Russia, which was also the cause of the split in the party. The reluctance to combine the Polish struggle for independence with a revolution in Russia is a complex issue. First of all, Piłsudski, and others activists of his group, did not believe in a swift success of Russian socialists. Both in his publications and those of members of his group, it is emphasized that according to them the crisis of the czarism is temporary and the democratic concessions were simply forced by circumstances. Thus, for Poles the events that took place in Russia could prove merely favourable, but not decisive for the Polish independence movement. The authors of "Trybuna” also polemicized strongly with the conception of “tri-annexation” - an idea to win the independence of all three annexed territories as a result of a great labour revolution, which - in turn - was to establish a federation of independent states in place of the overthrown monarchies. The activists of the Faction considered such a program to be not only a utopia, but also an act of high treason as it excluded the possibility of gaining independence even in one of the annexed territories and it would result in a federation of states, which would limit the political independence of Poland. Another matter which divided activists of PPS were the methods of revolutionary struggle and issues related with party tactics - especially after the revolution of 1905. To put it simply, we can find that - as far as parly tactics is concerned - the faction of “the young”, especially since the beginning of 1905, was in favour of mass campaigns, labour protests and strike campaigns. Whereas according to Piłsudski, the party should be concerned with stimulating the labour movement and controlling it, so that premature demonstrations would not take place as it could weaken the powers of the proletariat and damage the cause of the struggle for independence. In his plans, PPS was supposed to change its focus from mass activities to terrorist-conspirational ones. “Trybuna” was being published until September 1907. The publication was stopped becausc of financial reasons as well as because it had fulfilled its objectives as the organ of the faction, i.e. in its articles the first principles of an official cohesive political programme of the newly established PPS-Frakcja Rewolucyjna (Revolutionary Faction) had been formulated.